Upaya Meningkatkan Hasil Belajar Matematika Siswa Kelas VIII-F SMP Negeri 22 Surabaya Melalui Penerapan Model Pembelajaran Problem Based Learning Tahun Pelajaran 2018-2019 - Arezqi Tunggal Asmana (LPPM STKIP PGRI Sidoarjo, 2018)
Students' experience in solving problems through discovery is a prerequisite for students' critical and analytical thinking in constructing their learning outcomes, so that a knowledge system process will be formed in their students' memories that is ready to be reused when such knowledge is needed. Less optimal student learning outcomes are caused by several factors, one of which is the low attention and lack of concentration of students in following mathematics learning. Teachers often provide lessons in the form of lectures and questions and answers, so students are less motivated to develop creative thinking skills in solving problems. The purpose of this study is to determine whether there is an increase in student mathematics learning outcomes after the implementation of problem based learning learning models. This type of research is classroom action research with two cycles, where each cycle consists of activities of planning, implementation, observation, and reflection. Data retrieval is carried out by a written test on two linear variables. This research was conducted in class VIII-F of SMP Negeri 22 Surabaya with 32 students.